Sexual behavior and associated factors in rural adolescents - Bárbara Cabral de Sousa; Rebeca Silva dos Santos; Katiuscy Carneiro Santana; Raquel Souzas; Álvaro Jorge Madeiro Leite; Danielle Souto de Medeiros (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To describe the sexual behavior and to identify associated factors in adolescents from rural communities in Bahia, Brazil. METHODS: This is a cross-sectional, population-based, and household-based study, carried out in 2015 with adolescents aged 10 to 19 years. We described the variables of sexual intercourse in life and in the last 12 months, age at first intercourse, condom use and number of partners, guidance on pregnancy, AIDS, or other sexually transmitted infections, and guidance on how to get condoms. The analysis was performed for the total sample and for the quilombola and nonquilombola strata. We used Poisson regression, with robust variance, to estimate the prevalence ratios for sexual intercourse in relation to the explanatory variables. RESULTS: A total of 390 adolescents were interviewed, of them 42.8% were quilombolas, 51.3% females, and the median age was 14.8 years. Of these adolescents, 26.4% reported sexual intercourse (28.1% quilombolas and 25.1% non-quilombolas), and the median age of the first relation was 15 years; 77.7% of them mentioned condom use in the last intercourse and more than half received guidance on pregnancy, AIDS, or other sexually transmitted infections and received no guidance on how to get free condoms. Age (PR = 1.42) and alcohol use experimentation (PR = 2.41) were positively associated with sexual intercourse after adjustment. In the quilombola stratum, age (RP = 1.37), having three or more close friends (PR = 1.37), and experimentation with alcohol (PR = 2.60) were associated. In the non-quilombola stratum, age (PR = 1.43), black persons (PR = 2.06), and alcohol use experimentation (PR = 2.68) were associated. CONCLUSIONS: Lack of information and exposure to behaviors such as alcohol use experimentation are conditions that need to be addressed in health promotion strategies and in strategies for the prevention of sexual health problems in rural adolescents. Intersectoral partnerships between education and health also need to be strengthened to promote the autonomous and safe exercise of sexuality in this population.